All-solid-state composite positive pole piece as well as preparation method and application thereof

By introducing terpene compounds into the composite positive electrode sheet of all-solid state batteries, combining the mixing and fibrosis process under high and low temperature conditions, the interface contact problems caused by the volume changes of the positive electrode active material and the problem of insufficient adhesive bonding strength are solved, and the circulation performance of all-solid state batteries is significantly improved.

CN119725368AActive Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411961540.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

During the circulation process, the interface contact deteriorates due to the volume contraction and expansion of the positive electrode active material, and the performance of the existing adhesive polytetrafluoroethylene cannot provide sufficient interface bonding force, affecting the circulation performance.

Method used

Using terpene compounds as additives, combined with positive electrode active materials, solid electrolytes and conductive agents, a composite positive electrode sheet with enhanced adhesion effect was prepared through mixing and fibrosis processes at high and low temperature conditions.

Benefits of technology

The interface contact between the components inside the pole sheet is significantly improved, the loss of the positive electrode solid contact is reduced, and the excellent long cycle capacity retention rate of all-solid state batteries is achieved, especially at room temperature and low external pressure conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725368A_ABST
    Figure CN119725368A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and particularly relates to an all-solid-state composite positive pole piece and a preparation method and application thereof, and the preparation method comprises the following steps: mixing a positive active material, a solid electrolyte and a conductive agent to obtain a first mixture; under a high-temperature condition, mixing an additive terpenoid with the first mixture to obtain a second mixture; under a low-temperature condition, mixing a binder with the second mixture to obtain a third mixture; and fiberizing the third mixture, and forming to obtain the composite positive pole piece. Compared with the prior art, the invention solves the problems in the prior art that the positive active material of the all-solid-state battery generates volume shrinkage and expansion to deteriorate interface contact, resulting in reduction of battery performance; and the problem that the adhesive polytetrafluoroethylene in a dry process cannot provide enough interface bonding force is solved. According to the scheme, the interface contact is effectively enhanced, and the loss of solid-solid contact of the positive electrode is remarkably reduced, so that the all-solid-state battery realizes excellent long-cycle capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to an all-solid composite positive electrode plate and a preparation method and application thereof. Background Art

[0002] In the field of new energy vehicles, the application of lithium-ion power batteries is becoming more and more widespread, and the length of the driving range has become a key bottleneck restricting its development. Improving the energy density of lithium-ion batteries is an effective strategy to alleviate range anxiety. All-solid-state lithium batteries, as one of the potential ultimate forms of commercial lithium batteries, can not only provide safer power battery solutions by replacing flammable liquid electrolytes with solid electrolytes, but also achieve higher energy density and better cycle performance. In all-solid-state batteries, the solid-solid interface contact inside the positive electrode is a key factor in determining the reversible capacity and capacity retention rate of the battery. Therefore, optimizing these solid-solid interfaces is crucial to improving the performance of all-solid-state batteries.

[0003] Typically, a composite positive electrode sheet is composed of a positive electrode active material, a solid electrolyte, a conductive agent, and a polymer binder. The material formula of the composite positive electrode sheet has a significant impact on the performance of the all-solid-state battery, among which the bonding properties of the binder play a decisive role in maintaining good contact between the solid components and the tightness of the solid-solid interface. At present, the preparation process of the positive electrode sheet is mainly divided into two types: wet process and dry process. The dry process does not require the use of solvents in the production process, thereby eliminating the complicated drying and solvent recovery steps, which not only effectively reduces production costs and reduces environmental pollution, but also facilitates precise control of the thickness of the electrode sheet.

[0004] However, all-solid-state batteries still face the following challenges:

[0005] 1. During the cycle of all-solid-state batteries, the volume shrinkage and expansion of the cathode active material due to the deintercalation and insertion of lithium ions may deteriorate the interface contact and lead to a decrease in battery performance. To ensure performance, a high external pressure of more than 50 MPa is usually required, which is inconsistent with the actual needs of the commercialization of all-solid-state batteries.

[0006] 2. The adhesive polytetrafluoroethylene (PTFE) commonly used in the dry process has defects. PTFE cannot provide sufficient interfacial adhesion between the positive electrode active material, solid electrolyte and conductive agent, so it cannot effectively ensure the solid-solid contact between the positive electrode active material and the solid electrolyte and conductive agent, resulting in poor cycle performance of all-solid-state batteries.

[0007] In view of the above problems, the present invention aims to provide a composite positive electrode sheet that significantly improves the cycle performance of all-solid-state batteries to improve these problems. Summary of the invention

[0008] The purpose of the present invention is to provide an all-solid composite positive electrode plate and its preparation method and application in order to solve at least one of the above problems, so as to solve the problem that the volume shrinkage and expansion of the positive electrode active material of the all-solid-state battery due to the deintercalation and extraction of lithium ions may deteriorate the interface contact, resulting in a decrease in battery performance; and the adhesive polytetrafluoroethylene in the dry process cannot provide sufficient interface adhesion between the positive electrode active material, the solid electrolyte and the conductive agent. This solution effectively enhances the interface contact between the components inside the plate, significantly reduces the loss of the positive electrode solid-solid contact during the battery cycle, so that the all-solid-state battery can achieve excellent long-cycle capacity retention.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] The first aspect of the present invention discloses a method for preparing an all-solid composite positive electrode sheet, comprising the following steps:

[0011] S1: mixing a positive electrode active material, a solid electrolyte and a conductive agent to obtain a first mixture;

[0012] S2: mixing the additive terpenoid compound with the first mixture under high temperature conditions to obtain a second mixture;

[0013] S3: mixing the binder with the second mixture under low temperature conditions to obtain a third mixture;

[0014] S4: Fiberizing the third mixture and forming it into the composite positive electrode sheet.

[0015] Preferably, in step S1, the positive electrode active material includes lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, sulfur, selenium, sulfide, selenide and halide; the mass fraction of the positive electrode active material in the first mixture is 68-78%.

[0016] Preferably, in step S1, the solid electrolyte includes an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte; the mass fraction of the solid electrolyte in the first mixture is 19-29%.

[0017] Preferably, in step S1, the conductive agent includes carbon black, conductive graphite, carbon fiber, carbon nanofiber, carbon nanotube and graphene; and the mass fraction of the conductive agent in the first mixture is 3%.

[0018] Preferably, in step S2, the additive terpene compounds include monoterpene compounds, sesquiterpene compounds and diterpene compounds; the mass fraction of the additive terpene compounds in the second mixture is 3-8%.

[0019] More preferably, in step S2, the additive terpene compound is camphene.

[0020] Preferably, in step S3, the binder includes PTFE; the mass fraction of the binder in the third mixture is 0.5-2%.

[0021] Preferably, in step S2, the high temperature condition is a temperature condition that makes the additive liquid (melted); in step S3, the low temperature condition is a temperature condition that makes the additive solid.

[0022] More preferably, in step S2, the high temperature condition is 60-80°C; in step S3, the low temperature condition is 10-30°C.

[0023] Preferably, in step S4, the fiberizing is to apply shear force to the third mixture, and the forming includes hot rolling.

[0024] More preferably, in step S4, the fiberizing comprises ball milling, mechanical stirring, air flow crushing and grinding, and the forming comprises multi-stage hot rolling.

[0025] The second aspect of the present invention discloses an all-solid composite positive electrode plate, which is obtained by any of the preparation methods described above.

[0026] The third aspect of the present invention discloses an application of the all-solid-state composite positive electrode plate as described above in an all-solid-state battery.

[0027] Preferably, in the all-solid-state battery, the negative electrode plate used may be a lithium-indium alloy negative electrode plate or a lithium titanate composite negative electrode plate; it may also be a silicon material, a graphite material, a hard carbon material, a soft carbon material, a doped carbon material, a composite material composed of silicon and graphite, hard carbon, soft carbon or doped carbon, a tin-based material, or an alloy negative electrode composed of indium, lithium, aluminum and at least two of the above metals.

[0028] Preferably, the all-solid-state battery includes an all-solid-state lithium battery and an all-solid-state sodium battery.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The composite positive electrode plate provided by the present invention utilizes the additive terpenoid compound to significantly enhance the adhesion effect between the components inside the plate. This enhanced adhesion ensures that even after long-term cyclic use, the components can still maintain close contact, effectively enhances the interface contact between the components inside the plate, and significantly reduces the loss of solid-solid contact inside the positive electrode, thereby enabling the all-solid-state battery to achieve excellent long-cycle capacity retention. As a result, the capacity retention rate of the positive electrode is significantly improved. Especially under room temperature and low external pressure conditions, the performance improvement effect brought about by the introduction of terpenoid compounds is particularly obvious, thereby enhancing the overall performance of practical all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the process of preparing the composite positive electrode sheet of the present invention;

[0032] Figure 2 This is a photo of the appearance of the self-supporting all-solid composite positive electrode sheet prepared in Example 1 of the present invention;

[0033] Figure 3 The charge-discharge cycle test results of the composite positive electrode sheets of Example 3 and Comparative Example 2;

[0034] Figure 4 The SEM images of the composite positive electrode sheets of Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0035] In order to further understand the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments described below are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] In the following description, unless otherwise specified, the reagents used are commercially available products in the art, and the methods used are well-known means in the art.

[0037] The present invention provides a composite positive electrode sheet that can significantly improve the cycle performance of an all-solid-state battery. The all-solid-state composite positive electrode sheet proposed by the present invention introduces a solid additive terpene compound (preferably camphene), which itself has little effect on charging and discharging, and can act as a bonding component in the positive electrode, so that the bonding state between active substances is better, thereby alleviating the loss of solid-solid contact between the positive electrode during the cycle, and significantly improving the positive electrode capacity retention rate. The schematic diagram of the process of preparing the all-solid-state composite positive electrode sheet of the present invention is as follows: Figure 1 As shown, the following steps are included:

[0038] S1. The positive electrode active material, the solid electrolyte and the conductive agent are mixed to obtain a first mixture;

[0039] S2. Under high temperature conditions, mixing the additive (terpenoid compound) and the first mixture to obtain a second mixture;

[0040] S3. At room temperature, mixing the PTFE binder and the second mixture to obtain a third mixture;

[0041] S4. Fiberize the third mixture and reshape it to obtain a self-supporting all-solid composite positive electrode sheet.

[0042] In the process of preparing the above mixture, after obtaining the first mixture, the additive is added at high temperature to mix, so that the additive is melted and liquid, which helps the additive to be evenly distributed and fully contact with the components in the composite positive electrode; if the positive electrode active material, solid electrolyte, conductive agent, additive and PTFE binder are directly mixed, the PTFE binder may be fibrous and agglomerated, which is not conducive to the uniform distribution of the components. Therefore, in this preparation process, the raw materials are added and mixed step by step as needed. Therefore, as a preferred embodiment, the above raw materials of the present application are added in sequence according to the above method.

[0043] In this application:

[0044] The positive electrode active material is selected from one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, sulfur, selenium, sulfide, selenide and halide positive electrode materials; based on the first mixture, the content of the electrode active material is 68-78wt%; more specifically, the positive electrode active material is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0045] The solid electrolyte is selected from one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte; based on the first mixture, the content of the electrolyte powder is 19-29wt%; more specifically, the solid electrolyte is selected from Li 5.5 PS 4.5 Cl 1.5 .

[0046] The conductive agent is selected from one or more of carbon black, conductive graphite, carbon fiber, carbon nanofiber, carbon nanotube and graphene; based on the first mixture, the content of the conductive agent is 3wt%; more specifically, the conductive agent is selected from carbon nanofiber.

[0047] The additive is selected from monoterpenes (C 10 H 16 ), sesquiterpenes (C15 H 24 ), diterpenes (C 20 H 32 ) and the like; more specifically, the additive is selected from camphene in bicyclic monoterpene, and the content of the additive camphene is 3wt% of the second mixture.

[0048] The PTFE binder is based on the third mixture and has a content of 0.5-2 wt %; more specifically, the content of the PTFE binder is 1 wt %.

[0049] The present application comprises fiberizing the third mixture to obtain a fiberized mixture; the fiberizing means is specifically to apply shear force to the third mixture, and the device for applying shear force includes but is not limited to at least one of a ball mill, a mechanical stirrer, an air flow pulverizer and other mixing equipment; in the present application, manual grinding is used to apply shear force; according to the present invention, the fiberized mixture is finally formed to obtain a self-supporting positive electrode sheet. The forming method described in the present application is specifically multi-stage hot rolling.

[0050] As a preferred embodiment, the method for preparing the self-supporting composite positive electrode sheet of the present invention is as follows: 0.8 Co 0.1 Mn 0.1 O2, solid electrolyte Li 5.5 PS 4.5 Cl 1.5 , conductive agent carbon nanofibers are mixed at a mass ratio of 68-78:19-29:3 at room temperature for 20 minutes, 3wt% of molten additive camphene is added at 60°C and mixed evenly, and after cooling to room temperature of 25°C, 1wt% of PTFE binder is added to initially disperse it evenly, and manually grind it for 25-35 minutes to achieve pre-fiberization of the PTFE binder. After preliminary fiberization, it is subjected to multi-stage hot rolling at 120°C to form a self-supporting composite positive electrode membrane.

[0051] The present application also provides an all-solid-state battery that achieves excellent long-cycle capacity retention, comprising a lithium-indium alloy negative electrode sheet or a lithium titanate composite negative electrode sheet, a solid electrolyte membrane, and the above-mentioned all-solid-state composite positive electrode sheet.

[0052] It should be noted that the battery negative electrode prepared in the present application can also be selected from silicon materials, graphite materials, hard carbon materials, soft carbon materials, doped carbon materials, composite materials composed of silicon and graphite, hard carbon, soft carbon or doped carbon, tin-based materials or indium, lithium, aluminum and alloy negative electrodes composed of at least two of the above metals; the battery prepared in the present application can also be an all-solid-state sodium battery.

[0053] The following takes all-solid-state lithium battery as an example:

[0054] All-solid composite positive electrode

[0055] The all-solid composite positive electrode sheet in the all-solid-state battery provided in the present application comprises a positive electrode active material, a solid electrolyte, a conductive agent, a PTFE binder and an additive camphene. The positive electrode active material can be one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, sulfur, selenium, sulfide, selenide and halide positive electrode materials. Specifically, the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 The solid electrolyte may be one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte. Specifically, the solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 The conductive agent may be one or more of carbon black, conductive graphite, carbon fiber, carbon nanofiber, carbon nanotube and graphene. Specifically, the conductive agent is carbon nanofiber. The additive may be monoterpene (C 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 ) and the like; specifically, the additive is camphene, and the melting point of the additive camphene is between 48 and 52°C.

[0056] Negative electrode

[0057] The negative electrode plate includes a current collector and a negative electrode material disposed on the current collector. The negative electrode active material in the negative electrode material can be a silicon material, a graphite material, a hard carbon material, a soft carbon material, a doped carbon material, a composite material composed of silicon and graphite, hard carbon, soft carbon or doped carbon, or a tin-based material. Graphite materials may include but are not limited to natural graphite (block graphite, flake graphite, earthy graphite), artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), etc.; silicon materials may include but are not limited to crystalline silicon, amorphous silicon and organic silicon. The negative electrode plate may also be a self-supporting lithium titanate composite negative electrode plate, indium, lithium, aluminum, and an alloy negative electrode composed of at least two of the above metals. In addition, the negative electrode current collector may include a copper foil, a stainless steel foil current collector, or other negative electrode current collectors commonly used in the art may be used.

[0058] The preparation method of lithium titanate composite negative electrode is as follows: the negative electrode active material lithium titanate Li4Ti5O 12 、Solid electrolyte Li 5.5 PS 4.5 Cl 1.5, conductive agent carbon nanofibers are mixed in a mass ratio of 64:31:5 at room temperature for 20 minutes, 1wt% of PTFE binder is added to initially disperse them evenly, and they are manually ground for 25 to 35 minutes to achieve pre-fiberization of the PTFE binder. After preliminary fiberization, they are subjected to multi-stage hot rolling at 120°C to form a self-supporting lithium titanate composite negative electrode membrane.

[0059] Solid electrolyte layer

[0060] The solid electrolyte layer is composed of a solid electrolyte and a binder, wherein the solid electrolyte is one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte. Specifically, the solid electrolyte is Li 5.5 PS 4.5 Cl 1.5 The binder is one or more of nitrile rubber, styrene butadiene rubber, linear triblock copolymer, polyvinylidene fluoride or polytetrafluoroethylene (PTFE), and specifically, the binder is PTFE. The mass ratio of the solid electrolyte to the binder in the solid electrolyte layer is 90-99.5:0.5-10, and specifically, Li 5.5 PS 4.5 Cl 1.5 The mass ratio of PTFE to PTFE is 99.5:0.5.

[0061] All-solid-state battery

[0062] The all-solid composite positive electrode sheet, solid electrolyte layer and negative electrode sheet are sequentially placed into the mold for assembly; after assembly, pressurize and tighten the nut at the top of the column to a constant pressure to obtain an all-solid-state battery. The assembly process is completed in a glove box with an argon atmosphere.

[0063] It should be noted that the all-solid-state battery prepared by the above method is an all-solid-state lithium battery. However, the battery prepared in this application can also be an all-solid-state sodium battery.

[0064] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.

[0065] The reagents and raw materials used in the present invention are commercially available.

[0066] The present invention has no special requirements for the assembly method of the above-mentioned battery, and an assembly method familiar to those skilled in the art can be used. In addition, the above-mentioned technical solution can be applied not only to commonly used all-solid-state lithium batteries, but also to various types of dynamic batteries such as all-solid-state sodium batteries.

[0067] Some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0068] Example 1

[0069] All-solid composite positive electrode

[0070] Weigh the positive electrode active material LiNi according to the mass ratio of 68:29:3 0.8 Co 0.1 Mn 0.1 O2, solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The conductive agent carbon nanofiber is manually ground and mixed at room temperature for 20 minutes, 3wt% of the molten additive camphene is added at 60°C and evenly mixed, and after the temperature drops to 25°C, 1wt% of the PTFE binder is added to preliminarily disperse it evenly, and the PTFE binder is manually ground for 25-35 minutes to achieve pre-fiberization of the PTFE binder. After the preliminarily fiberization, it is subjected to multi-stage hot rolling at 120°C to form a self-supporting composite positive electrode membrane. The positive electrode active material surface loading of the composite positive electrode is 27.5mg / cm 2 .

[0071] like Figure 2 As shown, the composite positive electrode plate prepared in the present application does not require any other substrate for support or attachment and can be self-supporting.

[0072] Negative electrode

[0073] The negative electrode is a lithium-indium alloy sheet (10 mm in diameter).

[0074] Solid electrolyte layer

[0075] The solid electrolyte (Li 5.5 PS 4.5 Cl 1.5 ) and a binder (PTFE); the mass ratio of the two is 99.5:0.5.

[0076] All-solid-state lithium battery

[0077] The all-solid-state lithium-ion battery is composed of the above-mentioned all-solid-state composite positive electrode sheet, negative electrode sheet, and solid electrolyte layer, and the preparation steps are as follows:

[0078] The all-solid composite positive electrode sheet, solid electrolyte layer and lithium-indium alloy sheet are sequentially placed in the mold for assembly; after assembly, the pressure is increased to 50MPa and the nut at the top of the column is tightened to a constant pressure to obtain an all-solid-state lithium battery. It should be noted that the assembly process is completed in an argon atmosphere glove box, and the diameters of the all-solid composite positive electrode sheet, solid electrolyte layer and lithium-indium alloy sheet are all 10mm.

[0079] The assembled all-solid-state battery was subjected to a cycle test at an operating pressure of 50MPa, a temperature of 55°C, and a rate of 0.5C.

[0080] Example 2

[0081] The preparation method is consistent with that of Example 1, except that the surface loading of the positive electrode active material in Example 2 is 32.6 mg / cm 2 The assembled all-solid-state battery was subjected to a cycle test at an operating pressure of 6MPa, a temperature of 55°C, and a rate of 0.5C.

[0082] Example 3

[0083] The preparation method is consistent with that of Example 1, except that the surface loading of the positive electrode active material in Example 3 is 10.8 mg / cm 2 The assembled all-solid-state battery was subjected to a cycle test at an operating pressure of 6MPa, a temperature of 30°C, and a rate of 0.5C.

[0084] Example 4

[0085] The preparation method is the same as that of Example 1, except that the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, solid electrolyte Li 5.5 PS 4.5 Cl 1.5 The mass ratio of carbon nanofiber and conductive agent is 78:19:3. The surface loading of positive electrode active material is 24.7 mg / cm 2 .

[0086] In addition, the negative electrode is a lithium titanate composite negative electrode.

[0087] The negative electrode active material is lithium titanate Li4Ti5O 12 、Solid electrolyte Li 5.5 PS 4.5 Cl 1.5 , conductive agent carbon nanofibers are mixed in a mass ratio of 64:31:5 at room temperature for 20 minutes, 1wt% of PTFE binder is added to initially disperse them evenly, and they are manually ground for 25 to 35 minutes to achieve pre-fiberization of the PTFE binder. After preliminary fiberization, they are subjected to multi-stage hot rolling at 120°C to form a self-supporting lithium titanate composite negative electrode membrane.

[0088] The assembled all-solid-state battery was subjected to a cycle test at an operating pressure of 2MPa, a temperature of 30°C, and a rate of 0.5C.

[0089] Example 5

[0090] The preparation method is consistent with that of Example 4, except that the surface loading of the positive electrode active material in Example 5 is 25.4 mg / cm 2 .

[0091] Example 6

[0092] The preparation method is consistent with that of Example 4, except that the surface loading of the positive electrode active material in Example 6 is 28.8 mg / cm 2 .

[0093] Comparative Example 1

[0094] The preparation method is consistent with that of Example 1, except that the all-solid composite positive electrode sheet in Control Example 1 does not contain the additive camphene (no additive is added during preparation), and the positive electrode active material surface loading is 39.4 mg / cm 2 .

[0095] Comparative Example 2

[0096] The preparation method is consistent with that of Example 1, except that the all-solid composite positive electrode sheet in Control Example 2 does not contain the additive camphene, and the surface loading of the positive electrode active material is 10.8 mg / cm 2 The assembled all-solid-state battery was subjected to a cycle test at an operating pressure of 6MPa, a temperature of 30°C, and a rate of 0.5C.

[0097] Figure 3 The charge and discharge effects of the composite positive electrode sheets prepared in Example 3 and Control Example 2 at a rate of 0.1C are compared. By comparison, it can be seen that the introduction of camphene into the composite positive electrode sheet will not lose the charge and discharge specific capacity of the positive electrode.

[0098] Figure 4 The SEM diagrams of the composite positive electrode sheets prepared in Example 1 and Comparative Example 1 respectively show that the addition of camphene can alleviate the solid-solid contact loss of the positive electrode active material and play a certain bonding role.

[0099] Table 1 is a comparison of the cycle performance of the dry-process composite positive electrode sheets prepared in Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2. It can be seen from Example 1 and Comparative Example 1 that, under the same conditions of 50 MPa, 55°C and 0.5C, the addition of camphene with a surface loading of 27.5 mg / cm 2 When the capacity retention rate is 99.8% after 100 cycles, the surface loading of camphene is 39.4 mg / cm 2 When the capacity retention rate is 86.1% after 100 cycles, it is shown that the addition of camphene inside the composite positive electrode can improve the capacity retention rate; in addition, by comparing Example 3 with Comparative Example 2, it can be seen that when the surface loading is 10.8 mg / cm 2When cycled under 6 MPa, 30°C and 0.5C, the capacity retention rate of Example 3 after 500 cycles can still reach 89.4%, while the capacity retention rate of Control Example 2 after 200 cycles is only 72.3%, indicating that the introduction of camphene at room temperature and low external pressure is more effective. In addition, Examples 4 to 6 all show that even under a lower external pressure of 2 MPa, the introduction of camphene can also enable the all-solid-state battery to have a better capacity retention rate.

[0100] Table 1 Comparison of cycle performance of Examples 1 to 6 and Comparative Examples 1 to 2

[0101]

[0102]

[0103] In summary, through the formula and preparation process of the camphene-containing composite positive electrode plate provided in this application, the additive camphene can be used to enable the components in the all-solid-state composite positive electrode plate to remain in close contact after long-term circulation, thereby significantly improving the long-cycle performance of the all-solid-state battery operating at a lower operating pressure.

[0104] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an all-solid composite positive electrode sheet, characterized in that: The steps include: S1: mixing a positive electrode active material, a solid electrolyte and a conductive agent to obtain a first mixture; S2: mixing the additive terpenoid compound with the first mixture under high temperature conditions to obtain a second mixture; S3: mixing the binder with the second mixture under low temperature conditions to obtain a third mixture; S4: Fiberizing the third mixture and forming it into the composite positive electrode sheet.

2. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S1, the positive electrode active material includes lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based oxide, sulfur, selenium, sulfide, selenide and halide; the mass fraction of the positive electrode active material in the first mixture is 68-78%.

3. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S1, the solid electrolyte includes an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte; the mass fraction of the solid electrolyte in the first mixture is 19-29%.

4. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S1, the conductive agent includes carbon black, conductive graphite, carbon fiber, carbon nanofiber, carbon nanotube and graphene; the mass fraction of the conductive agent in the first mixture is 3%.

5. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S2, the additive terpene compounds include monoterpene compounds, sesquiterpene compounds and diterpene compounds; the mass fraction of the additive terpene compounds in the second mixture is 3-8%.

6. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S3, the binder includes PTFE; the mass fraction of the binder in the third mixture is 0.5-2%.

7. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S2, the high temperature condition is a temperature condition that makes the additive in liquid state; in step S3, the low temperature condition is a temperature condition that makes the additive in solid state.

8. The method for preparing an all-solid composite positive electrode sheet according to claim 1, characterized in that: In step S4, the fiberizing is to apply shear force to the third mixture, and the forming includes hot rolling.

9. An all-solid composite positive electrode plate, characterized in that: The method is adopted as claimed in any one of claims 1 to 8.

10. Use of the all-solid-state composite positive electrode sheet as claimed in claim 9 in an all-solid-state battery.

Citation Information

Patent Citations

  • Terpene resin based aqueous binder and application thereof to lithium ion battery cathode or super capacitor

    CN104017520A

  • Dry-method electrode plate containing solid electrolyte as well as preparation method and application of dry-method electrode plate

    CN115377424A

  • Preparation method of self-supporting pole piece and dry-method electrode pole piece

    CN115548243A

  • All-solid-state composite positive pole piece and all-solid-state battery

    CN118588867A

  • High-load dry-process composite positive pole piece and preparation method thereof

    CN118841521A

Cited By

  • Preparation method of self-supporting pole piece and dry-method electrode pole piece

    CN115548243A

  • A method for preparing a self-supporting electrode and a dry electrode sheet

    CN115548243B